Factors associated with treatment adherence to treatment among in patients with type 2 diabetes in Iran: A cross-sectional study - Nasrin Pourhabibi; Bahram Mohebbi; Roya Sadeghi; Elham Shakibazadeh; Mojgan Sanjari; Azar Tol; Mehdi Yaseri (Frontiers Media S.A., 2022)
IntroductionDiabetes is a chronic metabolic disorder that affects millions of people worldwide. Adherence to treatment is a key determinant to proper management. This study aimed to assess the factors associated treatment adherence in patients with type 2 diabetes.Materials and methodsWe conducted this cross-sectional study on 704 patients with type 2 diabetes referred to three diabetes clinics in Kerman, Iran. We used treatment adherence questionnaire and functional communicative critical health literacy (FCCHL) to collect data and descriptive statistics, as well as Pearson correlation coefficient and multivariate regression analysis to analyze data. Significance level was <0.05.ResultsThe study results showed that health literacy, HbA1c, and income were main predictors of diabetes treatment adherence. The patients' adherence increased as their health literacy increased. The patients' HbA1c decreases as their adherence increased. We found a 2.54-point increase in the treatment adherence score for those with sufficient income and a 0.76-point increase in the treatment adherence score for those with relatively sufficient income compared with those with insufficient income.ConclusionWe found several factors affecting diabetes treatment adherence. Planning theory-based interventions can be helpful to improve the determinants.